Journal of hydrologic engineering. - American Society of Civil Engineers. Water Resources Engineering Division (New York: American Society of Civil Engineers, 1996)
The Journal of Hydrologic Engineering disseminates information on the development of new hydrologic methods, theories, and applications to current engineering problems. The journal publishes papers on analytical, numerical, and experimental methods for the investigation and modeling of hydrological processes
Keywords: Hydraulic engineering -- -- Periodicals; Hydrology -- -- Periodicals